ANALYSIS FACTORS OF CAESAREAN SECTION - Rima Novianti; Dhea Nadya Putri (Journal of Maternity Care and Reproductive Health, 2020)
Sectio Caesarea (SC) surgical process to deliver a fetus through slices on the abdominal wall and walls. WHO sets the average standard of cesarean section in a country is about 5-15% per 1000 births in the world. The increase in childbirth with SC across the country occurred from 2007 to 2008 of 110,000 per birth in Asia. The purpose of the study was to find out the factors that most influence cesarean sectional. The design of this study used a cross-sectional approach with 82 respondents. The sampling technique was total sampling. The results showed that  63.4% of respondents were in reproductive age, mature gestational age was 59.7%, respondents in risky pregnancies were 62.1%, the history of cesarean surgery was 57.3%, and the distance between pregnancies less than two years (56%). The study found a relationship between maternal age (p: 0.008), gestational age (p: 0.003), risky pregnancies (p: 0.000), history SC (p: 0.040) with cesarean surgery. Meanwhile, no relationship between the distance of pregnancies (p: 0.063) and cesarean surgery. The Odds Ratio of risky pregnancy variables was 6.3. It can be concluded that mothers who have a risky pregnancy would labor with SC 6 times higher than other variables. Pregnancy is a happy time, so it needs to be planned by every couple, then the process of childbirth and breastfeeding can be passed safely.